Contralateral facial artery myomucosal island flap for the reconstruction of T2-T3 oncologic oral defects - Huang, Min; Li, Peiyao; Yang, Le; Xiao, Yudong; Zeng, Lingchan; Su, Yuxiong; Liang, Yujie; Zeng, Gucheng; Liao, Guiqing; Zhang, Sien (Frontiers in Oncology, 2024)
Objectives To avoid the oncologic risks of ipsilateral regional flaps, this study aimed to explore the feasibility and clinical outcomes of the contralateral-based facial artery myomucosal island flap (C-FAMMIF) for oral T2–T3 oncologic defects reconstruction. Methods A study of flap anatomy was conducted on 7 cadaver samples and a cohort of 24 patients who received C-FAMMIF reconstruction after malignancy resection were retrospectively researched. A balanced anterolateral thigh flap (ALT) group of 47 patients was extracted as control group using propensity score matching method. Progression-free survival (PFS), functional outcomes, and donor site complications were assessed. Results Consistent blood supply and drainage through facial artery and vein with median maximum pedicle length of 106 mm supported contralateral reconstruction. The superficial vein drainage pattern indicated safer flap harvest at contralateral neck under circumstances of ipsilateral neck dissections. The pedicle and marginal facial nerve formed three anatomical patterns. The surgical management of each was described. Patients with ipsilateral pN+ neck accounted for 41.7% and 40.4% in the C-FAMMIF and ALT group, respectively. The 2-year PFS rate between the C-FAMMIF and ALT groups was not significantly different (88.2% in C-FAMMIF group and 84.6% in ALT group, respectively, p = 0.6358). Promising recoveries were observed for swallowing function and tactile sensation. The donor sites healed upon primary closure without trismus or permanent facial palsy. Conclusion Our findings suggested that C-FAMMIF is feasible and safe for T2-T3 oral oncologic defect reconstruction in patients with ipsilateral cN+ neck.